2009
DOI: 10.1007/s10562-009-9862-9
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Nanocrystal Deposition for Higher Degree of Reduction in Co/Al2O3 Catalyst

Abstract: Alumina supported 5% Co catalyst was prepared, by the controlled nanocrystal deposition method using oleic acid as a capping agent, and tested for its activity and selectivity in Fischer-Tropsch synthesis. The catalyst exhibited facile reducibility of the cobalt species. The CO conversion and C 5? selectivity obtained on this size-controlled catalyst were higher than those observed on the catalysts prepared by impregnation and precipitation techniques. Decrease in the mobility of the nanoparticle towards the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Incomplete reduction of Co/Al 2 O 3 catalysts is commonly cited in literature. 44,54,55 Guczi et al reported a similar finding in his study of Pt-Co bimetallic catalysts. They concluded that the ratio of TPR peaks corresponding to Co 3 O 4 to CoO and CoO to Co 0 was not 1 : 3 due to redispersion of the Co 2+ ions spreading over the alumina, increasing the amount of Co surface spinel phase.…”
Section: Resultssupporting
confidence: 64%
“…Incomplete reduction of Co/Al 2 O 3 catalysts is commonly cited in literature. 44,54,55 Guczi et al reported a similar finding in his study of Pt-Co bimetallic catalysts. They concluded that the ratio of TPR peaks corresponding to Co 3 O 4 to CoO and CoO to Co 0 was not 1 : 3 due to redispersion of the Co 2+ ions spreading over the alumina, increasing the amount of Co surface spinel phase.…”
Section: Resultssupporting
confidence: 64%
“…the catalytic conversion of synthesis gas (an H 2 /CO mixture) into hydrocarbon fuels and chemicals . The cobalt-catalyzed FT reaction is reported to be structure sensitive, related to both cobalt particle size , and cobalt crystal structure. So far, most research involving Co-NC for FT concentrated either on slurry-phase FT, in which the unsupported Co-NC remain in suspension, or on Co-NC supported on irreducible oxides (mainly SiO 2 or Al 2 O 3 ). However, reducible oxides such as TiO 2 are also interesting supports for cobalt-based FT catalysts, for both industry and academia …”
Section: Introductionmentioning
confidence: 99%
“…The CO conversion and product distribution are mainly affected by the cobalt particle size, degree of reduction, reoxidation of metallic cobalt, and wax/coke deposition on FTS catalysts [10][11][12] ; however, the cobalt particle size above 6-8 nm has little effect on the enhancement of the intrinsic activity, such as turnover frequency (TOF) values. [13] The high initial activity at 10 h on stream with a low C 5 + selectivity (i.e., high CH 4 formation as shown in Table S1) could be attributed to the high reducibility of Co 3 O 4 particles and the presence of small cobalt particles.…”
Section: Resultsmentioning
confidence: 99%
“…During the FTS reaction, the morphology of cobalt particles is known to be altered significantly depending on the reaction conditions, and it also affects the rate of catalyst deactivation. [1] In steady-state FTS reaction, the observed higher CO conversion around 85.3 % and C 5 + selectivity around 87.9 % on the CoZrP(0.5) catalyst are possibly attributed to a redispersion of cobalt particles and a low mobile nature of cobalt particles on SiO 2 or Al 2 O 3 support [8,12] with high reducibility. The TOF or site-time yield (defined as the number of converted CO mole-cules per surface cobalt atom per s, s À1 ) on supported cobaltbased catalysts [14] is generally reported in the range of 1.6 10 À2 -3.0 10 À2 s À1 , and the value is similar on CoZrP catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation